Fair value accounting: The eternal debate – AinE EAA Symposium, May 2018 - Mora, A; McGeachin, A; Barth, M; Barker, R; Wagenhoffer, A; Joos, P (Taylor and Francis, 2019)
The last financial crisis led to a vigorous debate still in place about the pros and cons of fair-value accounting (FVA). While detractors basically argue its potential negative impact on procicality and financial stability or inadequacy in illiquid markets or specific business models, the International Accounting Standards Board (IASB) pushed to extend FVA in the new financial instruments standard and issued IFRS 13 to clarify its meaning and application. Some empirical research shows the usefulness of fair value accounting information to investors and contradicts its negative impact on stability, while other studies argue about its limitations in the contracting and stewardship role of accounting. The panelists of this symposium will present their views to contribute to the debate, which should be of interest not just to academic researchers, but also to practitioners and standard setters to deal with implementation issues and potential needs to address in the standards.